The role of Japan-India relations in the realization of F. Kishida’s “new realism” policy - Dobrinskaya O.A. (Восточная Азия: факты и аналитика)
The article examines the dynamics of Japanese-Indian relations during the Prime Minister Fumio Kishida's tenure in Japan. The realist approach, which seems to be the most suitable for analyzing the “diplomacy of realism” proclaimed by the Japanese leadership, is chosen as an analytical prism. Particular attention is paid to the political aspects of relations, as well as security issues and economic cooperation.Kishida Fumio returned the dynamics inherent in the bilateral dialogue during Shinzo Abe's time in power and temporarily lost under Prime Minister Suga Yoshihide, and continued developing relations in a wide range of areas. In general, F. Kishida's policy towards India demonstrates continuity, which indicates the stability of S. Abe's pragmatic course towards rapprochement. Despite the divergence of positions on the Ukrainian issue, bilateral ties remain strong due to the presence of common interests in the political and economic spheres. Japan considers India a like-minded country and a Quad ally, seeing it as a counterweight to China in the region.